2015
DOI: 10.5194/bg-12-961-2015
|View full text |Cite
|
Sign up to set email alerts
|

Drought in forest understory ecosystems – a novel rainfall reduction experiment

Abstract: Abstract. Precipitation patterns across Central Europe are expected to change over the 21st century due to climate change. This may reduce water availability during the plantgrowing season and hence affect the performance and vitality of forest ecosystems. We established a novel rainfall reduction experiment on nine sites in Germany to investigate drought effects on soil-forest-understory ecosystems. A realistic, but extreme annual drought with a return period of 40 years, which corresponds to the 2.5 % percen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…However, there was a significantly positive correlation between fine root decomposition rate and soil temperature, which was, therefore, the major driver of fine root decomposition, similar to that found in previous studies [57,[62][63][64][65][66]. According to Cusack et al [62], precipitation-related parameters are strong predictors of litter decomposition in neotropical forests, and Hobbie et al [67] also suggested that moister soils could facilitate rapid mass loss by promoting leaching and microbial activity or a faster colonisation of decomposing material by microbes.…”
Section: Soil Factors Influences On Fine Root Traitssupporting
confidence: 77%
“…However, there was a significantly positive correlation between fine root decomposition rate and soil temperature, which was, therefore, the major driver of fine root decomposition, similar to that found in previous studies [57,[62][63][64][65][66]. According to Cusack et al [62], precipitation-related parameters are strong predictors of litter decomposition in neotropical forests, and Hobbie et al [67] also suggested that moister soils could facilitate rapid mass loss by promoting leaching and microbial activity or a faster colonisation of decomposing material by microbes.…”
Section: Soil Factors Influences On Fine Root Traitssupporting
confidence: 77%
“…In our rainfall exclusion experiment drought stress was not intense enough to induce mortality or strong changes in aboveground biomass of a particular species (Gimbel et al, 2015). Nevertheless, drought and water repellency may promote the die-off of fine roots, which thereupon contribute to the total organic matter in the soil.…”
Section: Water Repellencymentioning
confidence: 99%
“…The resulting annual target precipitation inputs under the roofs were 700 mm (26 % reduction) for Schwäbische Alb, 355 mm (33 % reduction) at the Hainich-Dün and 395 mm (27 % reduction) at the Schorfheide-Chorin site. For a more detailed description of the whole experimental drought setting and of the study plots see Gimbel et al (2015).…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations